Kepribadian Tokoh Ana Dalam Novel Pelangi Dan Hujan Antara Kenangan Dan Angan Angan Karya Orina Fazrina - Septy Widya Larasati; Rangga Surya Fajri; Eva Dwi Kurniawan (Lembaga Pengembangan Kinerja Dosen, 2024)
This study employs a qualitative approach with a descriptive method, where the data analyzed consists of words and quotations taken from the novel